Innovations in In-House Development Systems at Tuanku Bainun Library, Universiti Pendidikan Sultan Idris - Sulaiman, Khairul Asyrani; Ramli, Siti Sumaizan (2015)
With the advance in information and communication technology (ICT), Tuanku Bainun Library of Universiti Pendidikan Sultan Idris (UPSI) has been enhancing the delivery systems in library services. This has led to the development of a number of in-house systems to improve user satisfaction and add value to library services and facilities. This paper discusses the innovation of four in-house systems namely Pustaka VRS (Vendor Rating System), SiberPROP, iPustaka and OffPAC. These systems have been developed since 2009 and are well received by library users. Further improvements and commercial potential aspects of these products are being studied.